A guide to Merleau-Ponty's Phenomenology of perception - Marshall, George J., 1949- (Marquette studies in philosophy ;, 2008)
This guide is based upon the belief that the best source for discovering what Merleau-Ponty has to say is what he, himself says. But the European style of writing and the dialectical form of argument present majors obstacles for the first time reader of this book. This guide attempts to overcome these problems by providing the reader with the necessary background, explanations of how the chapters of the book fit together, maps of the structure of the arguments of each chapter, a glossary of technical philosophical and psychological terms, and a useful bibliography. These things do not replace nor are they an alternative to reading the Phenomenology of Perception. However, A Guide to Merleau-Ponty's Phenomenology of Perception, is to provide the first time reader with the basic tools necessary for reading this important work.--Publisher description.